2020
DOI: 10.1177/0020764020972131
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress, mental health, and self-efficacy among community mental health workers: A cross-sectional study during COVID-19 pandemic

Abstract: Background: During the COVID-19, community mental health care workers (CMHWs) faced much heavier workloads, which make them vulnerable to mental problems. Aim: This study aims to investigate coronavirus disease-related occupational stress and its single and cumulative effect on mental health and self-efficacy among CMHWs. Methods: A quick-response online cross-sectional survey WA conducted during the coronavirus disease outbreak. A total of 536 CMHWs were recruited in March 2020, in China. Demographics, occupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 40 publications
2
55
0
Order By: Relevance
“…Demographic information form and occupational Stress Questionnaire (health and safety executive (HSE) tool indicator) were used to collect the data. The health and safety executive (HSE) questionnaire has 35 questions and 7 areas, which was developed in the 1990s by the British Institute for Health and Safety to measure occupational stress [ 26 ]. These seven areas are: 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic information form and occupational Stress Questionnaire (health and safety executive (HSE) tool indicator) were used to collect the data. The health and safety executive (HSE) questionnaire has 35 questions and 7 areas, which was developed in the 1990s by the British Institute for Health and Safety to measure occupational stress [ 26 ]. These seven areas are: 1.…”
Section: Methodsmentioning
confidence: 99%
“…Chirico et al also stated that in medical centers due to high workload, lack of employed personnel, as well as direct exposure to the pathogen COVID-19 and also observing the death of patients without receiving support from relatives, the possibility of depression and burnout in staff employed in these centers is higher [ 25 ]. According to a study by Sun et al, conducted on mental health care staffs in hospitals, staff serving quarantine suspects had a higher risk of depression and anxiety, as well as staying away from home for more than 3 days was identified as a risk factor for aggravation of anxiety and stress [ 26 ]. In addition, in the studies of Mirzaei Aliabadi et al, the stress factor was identified as an effective and aggravating factor of human error, the presence of which increases the likelihood of human error in the staff 27 , 28 .…”
Section: Introductionmentioning
confidence: 99%
“…We also emailed the authors of 43 articles that missed critical information and were able to get the information to include 10 additional studies. Altogether, the process generated 131 articles for this meta-analysis (An et al, 2020; Ben-Ezra et al; Cai et al; Cao et al, 2020; Chen et al; Chen et al; Chen et al; Chen et al; Chen et al, 2020; Cheng et al; Choi et al; Dai, 2020; Dong et al, 2020; Du et al, 2020; Elhai et al, 2020; Fang et al, 2020; Feng et al, 2020; Fong et al, 2020; Fu et al, 2020; Gao, 2020; Guo et al, 2020; Guo, 2020; Han et al, 2020; Hong et al, 2020; Hou et al, 2020; Hu et al, 2020a; Hu et al, 2020b; Huang et al, 2020a; Huang et al, 2020c; Huang et al, 2020d; Jin et al, 2020; Juan et al, 2020; Lai et al, 2020; Lam et al, 2020; Lei et al, 2020; Leng et al, 2020; Li; Li et al, 2020a; Li et al, 2020b; Li et al, 2020c; Li, 2020a; Li et al, 2020d; Li et al, 2020e; Li, 2020b; Li et al, 2020f; Li et al, 2020g; Liang et al, 2020; Lin et al, 2020a; Lin et al, 2020b; Liu, 2020; Liu, in press; Liu et al, 2020a; Liu et al, 2020b; Liu et al, 2020c; Liu et al, 2020d; Liu et al, 2020e; Liu et al, 2020f; Lu et al, 2020a; Lu et al, 2020b; Lu et al, 2020c; Mi et al, 2020; Ni et al, 2020a; Ni et al, 2020b; Ning et al, 2020; Pan et al, 2020a; Pan et al, 2020b; Qi, 2020; Qian et al, 2020; Qian, 2020; Qiu et al, 2020; Que et al, 2020; Ren et al, 2020b; Shi et al, 2020; Si et al, 2020; Song et al, 2020; Song, 2020; Su et al, 2020; Sun et al, 2020a; Sun, 2020; Sun et al, 2020b; Sun et al, 2020c; Tan et al, 2020; Teng et al, 2020; Tu et al, 2020; Wang et al, 2020a;…”
Section: Resultsmentioning
confidence: 99%
“…Relevant studies have also shown that, in groups such as firefighters ( 35 ), police officers ( 36 ), medical staff ( 37 ), and workers ( 38 ), the level of occupational stress affected the mental health status to different degrees. In addition, other studies ( 39 , 40 ) have shown that during the extraordinary period of the COVID-19 pandemic, anesthesiologists, community workers, and other groups also experienced a high level of occupational stress, which led to anxiety, depression, and the onset of other symptoms. This may be related to the special working environment of oil workers who are subjected to a harsh and unaccommodating climate, which is only hospitable to a relatively boring and monotonous life.…”
Section: Discussionmentioning
confidence: 99%